Microwave-assisted hydrothermal synthesis of magnetite nanoparticles with potential use as anode in lithium ion batteries - Xavier, Camila Soares [UNESP]; Paskocimas, Carlos Alberto; Motta, Fabiana Villela Da; Araújo, Vinícius Dantas; Aragón, Maria José; Tirado, José Luís; Lavela, Pedro; Longo, Elson [UNESP]; Delmonte, Mauricio Roberto Bomio (ABM, ABC, ABPol, 2014)
Rechargeable solid-state batteries have long been considered an attractive power source for a wide variety of applications, and in particular, lithium-ion batteries are emerging as the technology of choice for portable electronics. One of the main challenges in the design of these batteries is to ensure that the electrodes maintain their integrity over many discharge-recharge cycles. Fe3O4 deserves great attention as one of the most important electrode active materials due to its high theoretical capacity (926 mAhg- 1), low cost, being environmental-friendly and naturally abundance in worldwide. A simple strategy to synthesize magnetite nanoparticles (Fe3O4) by microwave-assisted hydrothermal method in a short processing time without further treatment is reported. The material obtained was tested as anode active material for lithium ions batteries. Impedance spectroscopy revealed that small differences in cell performance on cycling observed between samples cannot be strictly correlated to cell resistance. A high reversible capacity of 768.5 mAhg- 1 at 1C over 50 cycles was demonstrated, suggesting its prospective use as anode material for high power lithium ion batteries.
Keywords: magnetite; nanoparticles; Microwave hydrothermal (MH); Lithium ion batteries; anode active material